Can working with the private for-profit sector improve utilization of quality health services by the poor? A systematic review of the literature - Hanson Kara G; Goodman Catherine A; Patouillard Edith; Mills Anne J (BMC, 2007)
Abstract Background There has been a growing interest in the role of the private for-profit sector in health service provision in low- and middle-income countries. The private sector represents an important source of care for all socioeconomic groups, including the poorest and substantial concerns have been raised about the quality of care it provides. Interventions have been developed to address these technical failures and simultaneously take advantage of the potential for involving private providers to achieve public health goals. Limited information is available on the extent to which these interventions have successfully expanded access to quality health services for poor and disadvantaged populations. This paper addresses this knowledge gap by presenting the results of a systematic literature review on the effectiveness of working with private for-profit providers to reach the poor. Methods The search topic of the systematic literature review was the effectiveness of interventions working with the private for-profit sector to improve utilization of quality health services by the poor. Interventions included social marketing, use of vouchers, pre-packaging of drugs, franchising, training, regulation, accreditation and contracting-out. The search for published literature used a series of electronic databases including PubMed, Popline, HMIC and CabHealth Global Health. The search for grey and unpublished literature used documents available on the World Wide Web. We focused on studies which evaluated the impact of interventions on utilization and/or quality of services and which provided information on the socioeconomic status of the beneficiary populations. Results A total of 2483 references were retrieved, of which 52 qualified as impact evaluations. Data were available on the average socioeconomic status of recipient communities for 5 interventions, and on the distribution of benefits across socioeconomic groups for 5 interventions. Conclusion Few studies provided evidence on the impact of private sector interventions on quality and/or utilization of care by the poor. It was, however, evident that many interventions have worked successfully in poor communities and positive equity impacts can be inferred from interventions that work with types of providers predominantly used by poor people. Better evidence of the equity impact of interventions working with the private sector is needed for more robust conclusions to be drawn.